2017
DOI: 10.1177/1535370217740860
|View full text |Cite
|
Sign up to set email alerts
|

Methionine adenosyltransferases in cancers: Mechanisms of dysregulation and implications for therapy

Abstract: Methionine adenosyltransferase genes encode enzymes responsible for the biosynthesis of S-adenosylmethionine, the principal biological methyl donor and precursor of polyamines and glutathione. Mammalian cells express three genes - MAT1A, MAT2A, and MAT2B - with distinct expression and functions. MAT1A is mainly expressed in the liver and maintains the differentiated states of both hepatocytes and bile duct epithelial cells. Conversely, MAT2A and MAT2B are widely distributed in non-parenchymal cells of the live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 90 publications
2
79
0
Order By: Relevance
“…Among the essential translocators, we identified the S-adenosylmethionine synthase MAT2A, which is involved in the synthesis of S-Adenosyl-Methionine, a major methyl donor. Methylation is a well-established epigenetic mark and suspected to be highly correlated to the etiology of hepatocellular carcinoma amongst other cancers (11). We show for the first time that nuclear localization of MAT2A is cell cycle dependent in proliferating cells.…”
mentioning
confidence: 60%
“…Among the essential translocators, we identified the S-adenosylmethionine synthase MAT2A, which is involved in the synthesis of S-Adenosyl-Methionine, a major methyl donor. Methylation is a well-established epigenetic mark and suspected to be highly correlated to the etiology of hepatocellular carcinoma amongst other cancers (11). We show for the first time that nuclear localization of MAT2A is cell cycle dependent in proliferating cells.…”
mentioning
confidence: 60%
“…MAT2B can induce the growth and survival of cancer cells, enhance tumor migration and play a carcinogenic role. The increased expression of MAT2B happens in human liver, colon, gastric, breast, pancreas and prostate cancer [ 67 ]. In addition to interacting with MAT II, the mutations of MAT2B can interact with other else proteins, for example, including HuR [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“… 19 While few studies have investigated TIMP3 in FTC and FTA, it has been reported to be downregulated in papillary thyroid cancer (PTC) but expressed in normal thyroid tissues. 19 In a study of TIMP3 regulation of migration, invasion, and in vivo tumorigenicity of thyroid tumor cells, Borrello et al 20 found that TIMP3 induced reduced metastatic activities of human thyroid cell line NIM1 by repressing angiogenesis and macrophage infiltration in PTC-derived NIM1 cell line, indicating that TIMP3 is involved in a negative regulatory role. 19 MAT2A mRNA level is post-transcriptionally regulated by methylated-HuR and non-methylated-HuR.…”
Section: Resultsmentioning
confidence: 99%
“… 30 From the results of the study, metalloproteinase-3 (TIMP3) gene was found to be downregulated in both FTC and FTA. TIMP3 have been previously reported to be downregulated in primary thyrocytes infected with RET/PTC1 retroviral vector 20 and hypermethylated in association with BRAF mutation. 31 Hypermethylation of TIMP3 leads to silenced expression and agrees with similar findings on papillary thyroid carcinoma (PTC)-derived tumor cell lines which reported increased reversal upon treatment with a demethylating agent (5-Aza-dC).…”
Section: Discussionmentioning
confidence: 98%